1989
DOI: 10.1088/0029-5515/29/6/015
|View full text |Cite
|
Sign up to set email alerts
|

Lower hybrid current drive efficiency in the JT-60 tokamak

Abstract: Lower hybrid current drive (LHCD) experiments on JT-60 have been carried out in parameter n̄;e = (0.6−1.6)×1019 m−3, Ip = 0.5−1.5 MA, BT = 2.7−4.5 T, PLH < 2.5 MW, f = 1.75 and 2.0 GHz, with and without NB heating (PNB < 6 MW), limiter and lower side single null divertor configurations, and narrow and wide spectra. The current drive efficiency increases with the volume averaged electron temperature ⟨Te⟩ and with decreasing Zeff and a high efficiency of ηCD ≡ n̄eRPIRF/PLH ≤ 2.65 × 1019 m−2·A·W−1 was achieved by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
1

Year Published

1992
1992
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 8 publications
1
31
1
Order By: Relevance
“…Effects on η * CD from some of the variables considered here have been found for other tokamaks also, but the contemporary variation of the other quantities implied in equation 4is almost never taken into account when comparing different plasmas. The efficiency improvement with T e was first noticed by Porkolab [15], further evidenced in JT-60 [16] and JT-60U [17], and confirmed in JET [18]. The increment of η CD with I p has been observed both in Tore Supra [19] and JT-60U [20], even though it is not considered as the effect of decreasing q a , a view which we favour instead.…”
Section: Regression Analysis Resultsmentioning
confidence: 63%
“…Effects on η * CD from some of the variables considered here have been found for other tokamaks also, but the contemporary variation of the other quantities implied in equation 4is almost never taken into account when comparing different plasmas. The efficiency improvement with T e was first noticed by Porkolab [15], further evidenced in JT-60 [16] and JT-60U [17], and confirmed in JET [18]. The increment of η CD with I p has been observed both in Tore Supra [19] and JT-60U [20], even though it is not considered as the effect of decreasing q a , a view which we favour instead.…”
Section: Regression Analysis Resultsmentioning
confidence: 63%
“…In JT-60, perpendicular charge exchange measurements indicate that injected 70 keV protons are accelerated up to 200 keV, with a tail temperature of ~6 0 keV [177]. Both passive channels and an analyser with a crossed beam geometry observe beam acceleration [176], which implies that a.t least some of the energetic ions are located near the plasma centre. The long decay time of the accelerated ions (-200 ms) supports this conclusion as well [177].…”
Section: Lower Hybrid Bandmentioning
confidence: 99%
“…According to the CD theory [10], LHCD efficiency increases with the square of the parallel resonant velocity, which is about 3.5 times of the thermal velocity  th = √𝑘𝑇 𝑒 /𝑚 𝑒 . The experimental results also demonstrated that the LHCD efficiency is a significantly increasing function of <Te> [11,12]. Fig.…”
Section: Lhcd Efficiency Improved By Ecrhmentioning
confidence: 76%